Firestone Liberia's battle against ebola - Feddersen, Timothy James, 1958- (SAGE Knowledge. Cases., 2017)
This case puts students in the shoes of the ebola response leadership teams of Firestone Liberia and its parent company, Bridgestone Americas, as they worked together to respond to the deadly 2014 ebola epidemic. While the companies had received positive press for their containment of the virus on their rubber farm in Liberia, which was home to 8,000 employees and 80,000 Liberian citizens, the situation off the property was worsening. With death counts rising and hospitals across the nation closing as staff caught the virus, the Liberian government declared a national state of emergency. The teams now faced the possibility that the government might attempt to take control of the farm's medical center. Students are invited to consider how they would balance a duty to care effectively for employees against the demands of the Liberian government and whether the company should try to fend off the government or cooperate to meet the government's demands? Students will learn how to do a methodical situation analysis that considers ethical obligations and strategic implications, and to distill their recommendation into a briefing for senior leadership.